Prevalence of Cardiovascular Disease and Risk Factors in the Chinese Population with Impaired Glucose Regulation: the 2007–2008 China National Diabetes and Metabolic Disorders Study - Yang, Z.; Xing, X.; Xiao, J.; Lu, J.; Weng, J.; Jia, W.; Ji, L.; Shan, Z.; Liu, J.; Tian, H.; Ji, Q.; Zhu, D.; Ge, J.; Lin, L.; Chen, L.; Guo, X.; Zhao, Z.; Li, Q.; Zhou, Z.; Shan, G.; Yang, W.; null (Experimental and Clinical Endocrinology & Diabetes, 2013)
Cardiovascular disease (CVD) is one of the most common chronic diseases in China. This aim of this study is to determine the prevalence of CVDs and risk factors in Chinese impaired glucose regulation subjects.We used a multistage, stratified sampling method to select subjects from the general Chinese population aged 20 years and older. Subjects underwent an oral glucose tolerance test to identify normal glucose tolerance (NGT) and impaired glucose regulation including isolated impaired fasting glucose (i-IFG), impaired glucose tolerance (i-IGT), and combined IFG/IGT and diabetic mellitus (DM). A logistic regression analysis was performed to examine the association between glucose abnormalities and CVD events.We identified that 34 293 subjects had NGT, 1 469 i-IFG, 4 571 i-IGT, 957 IFG/IGT and 4 949 DM. The age-sex standardized prevalence rate of cardiovascular disease was 1.06% (95% CI 0.87–1.28), 1.79% (95% CI 1.37–2.33) and 3.83% (95% CI 2.79–5.24) in NGT, impaired glucose regulation and DM, respectively. Among impaired glucose subjects, prevalence of defined CVD risk factors (smoking, overweight, obesity, hypertension and dyslipidemia) was 29.52% (95% CI: 27.8–31.21), 36.25% (95% CI: 34.29–38.26), 10.05% (95% CI: 8.86–11.37), 36.43% (95% CI: 34.53–38.36) and 69.96% (95% CI: 67.87–71.98), respectively. Compared to 1 risk factor, the odds ratios (ORs) of CVDs with 2, 3 or 4 risk factors were 1.94 (95% CI: 0.74–5.09), 2.76 (95% CI: 1.06–7.21) and 5.84 (95% CI: 1.68–20.26), respectively. Additionally, compared to i-IFGs, ORs of CVDs with i-IGT and IFG/IGT were 2.88 (95%CI 1.36–6.01) and 2.12 (95% CI 0.83–5.44), respectively.The prevalence of cardiovascular risk factors was high in the Chinese impaired glucose regulation population. The postprandial hyperglycemia is more associated with CVD than isolated fasting hyperglycemia.
Keywords: diabetes; cardiovascular risk management; metabolic features